The effect of internal audit on accounting disclosure in Jordanian banks - Norsiah, Ahmad; Syamsul Azri, Abdul Rahman (2018)
This paper focuses on identifying most in influencing factors of internal audit on the accounting disclosure in Jordanian Commercial Banks (JCBs). The perceptions of JCBs' internal auditors have been investigated. In general it was found that the respondents believe that the role of the internal auditor in the accounting disclosure in the Jordanian banking sector ranges from satisfactory to very good. The results indicate a positive and significant correlation between accounting disclosure and the proficiency of auditor. The results of this study make a contribution to existing literature in the area of factors affecting the role of the internal auditor in the accounting disclosure in eastern developing countries such as Jordan. In addition, this research adds further evidence to the value of studying auditing efficiency.